Experimental study on fly ash and lead smelter slag-based geopolymer concrete columns. (15th June 2017) - Albitar, M.; Mohamed Ali, M.S.; Visintin, P.
Highlights: Granulated lead smelter slag (GLSS) can be used in structural applications. GLSS concrete columns has similar failure mode to that of OPC concrete. The current design provisions can be modified and used for geopolymer concrete. Abstract: Geopolymer concretes have emerged as novel engineering materials with the potential to significantly reduce the environmental footprint of concrete manufacture and utilise high volume of industrial waste materials. Although significant experimental research has focused on the development of geopolymer mix design, there is far less information available regarding the performance of geopolymer concretes at a member level. This has implications in transferring geopolymer concretes from a laboratory material to a material in which can be specified in practice. This paper addresses the application of geopolymer concrete at a member level through an experimental investigation on the behaviour of fly ash/granulated lead smelter slag (GLSS)-based geopolymer concrete columns and beams tested under concentric and eccentric loading. Slenderness effect of the geopolymer concrete columns is investigated and axial load-moment interaction envelopes are generated experimentally. The analytical interaction diagrams are compared to those calculated using classical methods for normal reinforced concrete beams and columns. The results of the comparison show that the analytical interaction diagrams overestimated the test results due to variation in material properties. Nevertheless, the results reveal that fly ash/GLSS-based geopolymer concrete exhibits similar structural behaviour to ordinary Portland cement (OPC) concrete. The results also highlight potential issues with the scaling of ambient-cured geopolymer concrete to the structural level.